Early detection of unhealthy behaviors, the prevalence and receipt of antiviral treatment for disabled adult hepatitis B and C carriers. (December 2016) - Jane, Sui-Whi; Lin, Ming-Shyan; Chiu, Wen-Nan; Lai, Li-Ju; Chen, Po-Han; Chen, Mei-Yen
Abstract Background Evidence indicates that hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are the leading causes of liver cirrhosis and hepatocellular carcinoma. Antiviral treatments have recently been reported as successful cures. However, the prevalence rates of HBV or HCV infection, unhealthy behaviors and receipt of adequate treatment in disabled adults have not been described. The aim of this study was to examine the prevalence of HBV or HCV carriers, receipt of antiviral treatment, and early detection of unhealthy behaviors in disabled adults in Taiwan. Methods A population-based, cross-sectional study was conducted between July and December 2013 with 845 community-dwelling adults with disabilities aged >20 years. Statistical analyses included descriptive statistics, Chi-squared tests, and stepwise regression analysis. Results The prevalence of HBV and HCV infections was 12.9 and 14.1 %, respectively. HCV carriers tended to be older (p  < 0.001) and with a lower education (p  < 0.001). The majority of HBV/HCV carriers did not know the type of hepatitis infection and did not receive adequate antiviral treatment. After adjusting for potential confounding variables, regression analysis showed that the factors significantly associated with elevated liver function were HCV infection (p  < 0.001), HBV infection (p  = 0.001), high fasting blood glucose levels (p  = 0.001), overweight (p  = 0.003), older age (p  = 0.027), and alcohol drinking (p  = 0.028). Conclusions There was a high prevalence of HCV infection among adults with disabilities; few received adequate antiviral treatment or early detection of unhealthy behaviors for the prevention of liver cancer. Clinicians can provide health education to help the participants and caregivers better understand the relationships between specific risk factors and liver health and can encourage HBV and HCV carriers to undergo annual physical check-ups and receive adequate treatment, as covered by the national health insurance.